Advancing ethnomusicological research efforts on female musicianship: a focus on Yoruba female dùndún drummers (2014)
One major area where Professor Mosunmola A. Omibiyi-Obidike has made a substantial scholarly mark to African musicology is in the study of female musicians. However, more than two decades after expressing her concern about a lack of in-depth musicological studies into and documentation of the contributions of female musicians to the growth and development of African music, there has not been any significant response on the part of Nigerian musicologists to heed this call. This dearth of information has often been attributed to both a combination of the male dominated field of African Studies and the patriarchal structures of communities usually being studied in Africa. This paper, therefore, is a modest attempt to set the tone for a fresh direction as it examines efforts of female dundun drummers at promoting an egalitarian and positivist modern African society. The discourse is limited to Ara and Ayanbinrin - two contemporary urban popular female dundun practitioners based in Lagos, Southwestern Nigeria. The paper posits that apart from being entertainers and promoters of culture, the female dundun musicians, judging by the themes of their music and the overall messages of their art, are also social engineers, teachers and instructors, mobilizers as well as nation builders among others.